2019
DOI: 10.1021/jacs.9b10526
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogen Atom Abstraction from Dihydroflavonol by a Nonheme Iron Center Is the Key Step in the Enzymatic Flavonol Synthesis and Avoids Byproducts

Abstract: The plant nonheme iron dioxygenase flavonol synthase performs a regioselective desaturation reaction as part of the biosynthesis of the signaling molecule flavonol that triggers the growing of leaves and flowers. These compounds also have health benefits for humans. Desaturation of aliphatic compounds generally proceeds through two consecutive hydrogen atom abstraction steps from two adjacent carbon atoms and in nature often is performed by a high-valent iron(IV)-oxo species. We show that the order of the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 133 publications
(307 reference statements)
6
84
0
Order By: Relevance
“…S3 and Table S2 in the ESI †). 128 Among all the states computed, the 2 1 hs-hs doublet state is found to be the ground state and this is followed by 10 1 hs-hs , 8 1 hs-is , 4 1 hs-is , 6 1 hs-ls , 8 1 ishs , 2 1 is-hs , 6 1 is-is , 2 1 is-is , 4 1 is-ls , 6 1 ls-hs , 4 1 ls-hs , 4 1 ls-is , 2 Table 1). Our energy calculations reveal that the Fe III (S a ) and Fe IV (S b ) centres possess a high spin state as their ground state, and these states are antiferromagnetically coupled leading to the S T ¼ 1/2 ground state, and this is also consistent with the experiments.…”
Section: Electronic Structure Of [Ho(l)fementioning
confidence: 94%
See 1 more Smart Citation
“…S3 and Table S2 in the ESI †). 128 Among all the states computed, the 2 1 hs-hs doublet state is found to be the ground state and this is followed by 10 1 hs-hs , 8 1 hs-is , 4 1 hs-is , 6 1 hs-ls , 8 1 ishs , 2 1 is-hs , 6 1 is-is , 2 1 is-is , 4 1 is-ls , 6 1 ls-hs , 4 1 ls-hs , 4 1 ls-is , 2 Table 1). Our energy calculations reveal that the Fe III (S a ) and Fe IV (S b ) centres possess a high spin state as their ground state, and these states are antiferromagnetically coupled leading to the S T ¼ 1/2 ground state, and this is also consistent with the experiments.…”
Section: Electronic Structure Of [Ho(l)fementioning
confidence: 94%
“…In the rst step, a weak reactant complex formation is assumed with the substrate, and the O/H interaction between O(1) and a hydrogen atom of the substrate. We have computed nine possible spin states with 2 RC hs-hs as the ground state, with the 10 RC hs-hs , 8 RC hs-is , 4 RC hs-is , 6 RC is-is , 2 RC is-is , 4 , respectively. Formation of species RC from the reactant is found to be slightly exothermic by À18.1 kJ mol À1 justifying the need to invoke such complex formation.…”
Section: First Hydrogen Atom Abstractionmentioning
confidence: 99%
“…Thus, in plants, flavonols are synthesized from dihydroflavonol through a desaturation reaction by a nonheme iron dioxygenase using dioxygen and α‐ketoglutarate . A recent computational study showed that, against chemical intuition, the enzyme abstracts the strongest of the two C−H bonds of the substrate first . It was shown that substrate positioning in the active site guided the reaction to the thermodynamically less favorable pathway, which is important as it drives the reaction to selective desaturation, whereas an initial hydrogen atom abstraction from the other position would lead to dominant substrate hydroxylation instead.…”
Section: Second‐coordination Sphere Effects In Nonheme Iron Enzymesmentioning
confidence: 99%
“…Consequently, substrate and oxidant positioning in flavonol synthase leads to dominant desaturated product rather than the thermodynamically more stable hydroxylated product. As such, nature has a range of nonheme iron enzymes that perform negative catalysis, whereby the thermodynamically favored pathway is blocked through stereochemical interactions and substrate and oxidant positioning in the active site …”
Section: Second‐coordination Sphere Effects In Nonheme Iron Enzymesmentioning
confidence: 99%
See 1 more Smart Citation